2021
DOI: 10.3389/fmed.2021.744697
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV2 Infection and the Importance of Potassium Balance

Abstract: SARS-CoV2 infection results in a range of symptoms from mild pneumonia to cardiac arrhythmias, hyperactivation of the immune response, systemic organ failure and death. However, the mechanism of action has been hard to establish. Analysis of symptoms associated with COVID-19, the activity of repurposed drugs associated with lower death rates or antiviral activity in vitro and a small number of studies describing interventions, point to the importance of electrolyte, and particularly potassium, homeostasis at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Potassium (K + ) efflux triggers the activation of the NLRP3 inflammasome upon infection by RNA viruses [ 303 ], including SARS-CoV-2 [ 362 , 363 ], where elevated urinary loss of potassium is often associated with COVID-19 disease severity [ 364 ]. Experimental work showed the SARS-CoV-2 ORF3a viroporin priming and activation of the NLRP3 inflammasome were dependent upon K + efflux [ 365 ].…”
Section: Melatonin Protects Mitochondria and Atp Production To Inhibi...mentioning
confidence: 99%
“…Potassium (K + ) efflux triggers the activation of the NLRP3 inflammasome upon infection by RNA viruses [ 303 ], including SARS-CoV-2 [ 362 , 363 ], where elevated urinary loss of potassium is often associated with COVID-19 disease severity [ 364 ]. Experimental work showed the SARS-CoV-2 ORF3a viroporin priming and activation of the NLRP3 inflammasome were dependent upon K + efflux [ 365 ].…”
Section: Melatonin Protects Mitochondria and Atp Production To Inhibi...mentioning
confidence: 99%
“…The expected contributing factor was vitamin D [ 60 ]. It is also suggested that potassium balance surprisingly influences COVID-19 severity [ 61 ]. These factors are likely not influenced by the ongoing climate changes though add complexity to the analysis and modeling.…”
Section: Amplification Of Biological and Social Factors Promoting Pot...mentioning
confidence: 99%
“…Previous research on COVID-19 patients indicated that hypokalemia is a frequent finding in these patients, and it may increase the risk of developing fatal arrhythmias [ 20 , 21 ]. Hypokalemia in SARS-CoV-2 infection may occur due to hyperactivation of the renin-angiotensin-aldosterone system, GI loss, lack of appetite because of concurrent illness, and damage of the tubules due to ischemia or nephrotoxic agents [ 22 ]. Moreover, hypokalemia can aggravate acute respiratory distress syndrome and affect myocardial function [ 23 ].…”
Section: Introductionmentioning
confidence: 99%